Improving Societal Resilience to Disasters A Case Study of London’s Transportation System - Atun, Funda. (PoliMI SpringerBriefs,, 2014)
This book documents the outcomes of a study designed to explore ways of increasing resilience in a complex city system against disasters by focusing on the transportation system in London. A survey was undertaken comprising interviews with upper level decision makers as well as questionnaires to personnel in the field and the general public. The results of this survey are presented, together with a brief description of the past and current situation in the city with respect to transportation, flood risk, and other vulnerabilities. The sources of problems in responding adequately to disasters are analyzed and important lessons drawn. In particular, it is explained how failures derive from insistence upon the application of written plans in preference over redefinition of strategies and priorities, and how flexible systems represent a better approach to crisis situations. The book will be of interest to all who are concerned with disaster planning and management and the societal response to disasters.